Properties and behavior of silica rock from east coast Malaysia region in crystal glass application - Ismail, Syarifah Aminah; Mustaffar, Mohd Idham (Thai Geoscience Journal, 2022)
Crystal glass is defined as colorless and translucent glass, which is generally applied as tableware utensils and art products, in compliance with the ASTM C162-56 standard method. Traditionally, crystal glass was manufactured using silica sand with SiO2 purity of not less than 99.5%. In this research, local silica rock acquired from the east coast of Malaysia region was utilized in the production of crystal glass. Previous studies revealed that raw silica rocks possess a good quality, but still inadequate to comply with the minimum requirements for crystal glass making. The purpose of this study was to improve the quality of silica rock via a physico-chemical method that comprised simultaneous attrition scrubbing and acid treatment. In this method, variable citric acid concentrations of less than 1%, and constant scrubbing time and speed of agitation of 20 minutes and 1250 rpm, respectively were implemented. Markedly, citric acid was found effective in improving the purity of SiO2, where 99.8% purity was successfully achieved at 0.75% acid concentration. XRD analysis revealed trigonal crystals system of SiO2 in the silica rock samples. By implementing the novel crystal glass formulation, crystal glass with density of ≥ 2.40 g/cm3 , Vickers hardness of 550 ± 20 kg.f/cm2 , and refractive index of ≥ 1.5 was successfully produced, which complied with the standard requirements of BS 3828:1973.